Human-AI Collaboration: Enhancing Productivity and Decision-Making - Akinnagbe, Olayiwola Blessing (International Journal of Education, Management, and Technology, 2024)
The integration of Artificial Intelligence (AI) into various sectors has catalyzed significant improvements in productivity and decision-making. This paper explores the collaborative potential between humans and AI, focusing on how this synergy can enhance both operational efficiency and decision-making accuracy. While AI excels in processing vast amounts of data and automating repetitive tasks, human capabilities in creativity, intuition, and emotional intelligence complement AI systems, enabling more nuanced and informed decisions. Through a comprehensive review of existing literature, case studies, and real-world applications, the paper examines how AI tools, such as predictive analytics, machine learning, and cognitive computing, support human decision-makers in fields such as healthcare, finance, and business. Despite the clear benefits, challenges persist, including technical integration issues, resistance to AI adoption, and ethical concerns related to bias and transparency. This paper proposes a framework for optimizing human-AI collaboration, emphasizing complementary roles and the development of hybrid intelligence systems. It concludes by identifying future research directions and policy implications, aimed at fostering more effective and ethical human-AI partnerships in the workplace.